Associated factors with dietary patterns among children under 2 years of age: a study in childcare centres and homes of South Brazil - Juliana R. D. Guedes; Doroteia A. Höfelmann; Fernanda P. Madruga; Elaine C. V. de Oliveira; Mônica M. O. de Cerqueira; Alline C. S. Lobo; Cláudia C. B. Almeida (Journal of Nutritional Science, 2021)
Identifying dietary patterns in different environments attended by children is relevant to guide public politics. The aim of this study was to analyse the factors associated with dietary patterns of children under 2 years of age in childcare centres and at homes. This transversal study was enrolled in municipal childcare centres of Guaratuba, Paraná, Brazil. Food consumption data from 256 children were obtained by the food record method. From the consumption data, four dietary patterns were identified by factor analysis using the principal component method in each environment. ‘Traditional’ patterns were observed in both environments; the ‘less healthy’ pattern was found only at homes. Other patterns identified in childcare centres include ‘snacks’, ‘nutritive’ and ‘pasta and meats’; at homes, it was possible to identify patterns such as ‘milk and cereals’ and ‘mixed’. Children over 12 months presented higher scores for all the patterns in both environments. Obese children had lower scores for all the patterns in childcare centres. There was an association between maternal age below 21 years and higher adherence to a ‘less healthy’ pattern, maternal level of education less than 8 years and lower adherence to the ‘mixed’ pattern and lower familiar income per capita and higher adherence to the ‘snacks’ and ‘traditional’ patterns in childcare centres. In conclusion, adherence to dietary patterns was associated with socio-economic, demographic variables and nutritional status and further studies are needed, especially those with a longitudinal design, enabling the monitoring of dietary patterns.